2010
DOI: 10.1038/oby.2009.256
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Catechin Enriched Green Tea on Body Composition

Abstract: Obesity is a major health problem in the developed and developing world. Many “functional” foods and ingredients are advocated for their effects on body composition but few have consistent scientific support for their efficacy. However, an increasing amount of mechanistic and clinical evidence is building for green tea (GT). This experiment was therefore undertaken to study the effects of a high‐catechin GT on body composition in a moderately overweight Chinese population. In a randomized placebo‐controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
143
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(154 citation statements)
references
References 41 publications
6
143
0
5
Order By: Relevance
“…The ingredients in green tea play a role in increasing energy metabolism, resulting in weight loss [24]. In a randomized controlled study, intake of high catechins green tea (468 mg catechins) by moderately overweight Chinese subjects for a period of 90 days lead to reduction in intra-abdominal fat, waist circumference reduction, reduction in body weight, total body fat and body fat % indicating improvements in body composition and reduction in abdominal fatness [25]. Another 12 week study from Japan among men and women with increased visceral adiposity, consumption of a beverage providing 583 mg/d of tea catechins were associated with significantly greater reductions in body weight, body fat, and abdominal fat mass compared with a control beverage providing 96 mg/d [26].…”
Section: Discussionmentioning
confidence: 99%
“…The ingredients in green tea play a role in increasing energy metabolism, resulting in weight loss [24]. In a randomized controlled study, intake of high catechins green tea (468 mg catechins) by moderately overweight Chinese subjects for a period of 90 days lead to reduction in intra-abdominal fat, waist circumference reduction, reduction in body weight, total body fat and body fat % indicating improvements in body composition and reduction in abdominal fatness [25]. Another 12 week study from Japan among men and women with increased visceral adiposity, consumption of a beverage providing 583 mg/d of tea catechins were associated with significantly greater reductions in body weight, body fat, and abdominal fat mass compared with a control beverage providing 96 mg/d [26].…”
Section: Discussionmentioning
confidence: 99%
“…Yeşil çay tüketen grubun glikoz ve demir seviyelerinin kontrol grubundan düşük olduğu, buna rağmen HDL kolesterol ve magnezyum seviyelerinin yüksek olduğu belirlenmiştir (42). Yapılan diğer çalışmalarda da yeşil çayın kilo kaybı meydana getirdiği belirlenmiştir (43)(44)(45). Bu çalışmalarda özellikle, 3 aydan daha uzun süreli yeşil çay tüketiminin beden ağırlığını ve yağını azaltmada etkili olduğu vurgusu yapılmıştır (12).…”
Section: Journal Of Contemporaryunclassified
“…In the 26 human experiments conducted by Hursel et al (2011) and Phung et al (2010), most of the investigations discovered that tea drinking could reduce BW. Wang et al (2010) investigated the influence of tea drinking on the waist circumference, and the results were that for overweight Chinese taking green tea polyphenol (caffeine <200 mg) 458-886 mg/d for 90 d, the body fat could be decreased. A trial involving 132 overweight or obese women over 12 weeks demonstrated a significant reduction in abdominal fat and subcutaneous abdominal fat area in the group that consumed green tea compared with the control group (Maki et al, 2009).…”
Section: Prevention Of Metabolic Syndrome (Mets) and Cardiovascular Dmentioning
confidence: 99%